Comparative economic value added on Southeast Asian banking industry - Lintang Dewanti; Rofikoh Rokhim (Universitas Islam Indonesia, 2017)
This study analyses the bank's performance comparison across countries in some ASEAN members which are listed in the stock exchange, as well as to analyse the influence of Economic Value Added (EVA) and some financial ratios on the company stock return. Analysis suggests some results. In Indonesia, Thailand and the Philippines, the movement of EVA follows the movement of Gross Domestic Product (GDP). This study also finds that Earning per Share (EPS), only in Singapore, and Return on Equity (ROE) and Return on Assets (ROA), only in the Philippines, have an influence on stock return. Only in the Philippines where EVA together with ROA has an effect on stock return.